Shining with the Stars: Competition, Screening, and Concern for Coworkers' Quality - Francesca Barigozzi; Helmuth Cremer (Institute of Labor Economics (IZA), 2021)
We study how workers' concern for coworkers' ability (CfCA) affects competition in the labor market. We consider two firms offering nonlinear contracts to a unit mass of prospective workers. Firms may differ in their marginal productivity, while workers are heterogeneous in their ability (high or low), and in their taste for being employed by any of the two firms. Workers receive a utility premium when employed by the firm hiring the workforce with larger average ability and they suffer a utility loss in the opposite case. These premiums/losses are endogenously determined. When workers' ability is observable and the difference in firms' marginal productivities is strictly positive, we show that CfCA increases surplus but it also increases firms' competition for high-ability workers. As a result, CfCA benefits high-ability workers but is detrimental to firms. In addition, CfCA exacerbates the existing distortion in sorting of high-ability workers to firms: too many workers are hired by the least efficient firm. When ability is not observable, the additional surplus appropriated by high-ability workers is eroded by overincentivization (countervailing incentives) and the more so when CfCA is high. Conversely, high-types' sorting improves when CfCA is low and remains the same when it is high.
Keywords: D82; L13; M54; 330; screening; competition; concern for coworkersâ exteuro™ quality; sorting